2022
DOI: 10.3389/fmed.2022.880285
|View full text |Cite
|
Sign up to set email alerts
|

Women in Rheumatology in the Arab League of Associations for Rheumatology Countries: A Rising Workforce

Abstract: BackgroundAn increase in women physicians in the medical workforce is witnessed in recent decades, paralleled by an increase in leadership positions and, to a lesser extent, in academic advancement.ObjectivesThis study aims to evaluate the women rheumatologists (WR) workforce and to identify the challenges faced by WR in the Arab League of Associations for Rheumatology (ArLAR) countries.MethodsWe collected data from members of special interest groups from 16 ArLAR countries about the number of rheumatologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Furthermore, the female-to-male rheumatologist ratio is very high in some countries and is expected to rise in the future [19]. This might raise some concerns for the workforce in general as the ACR workforce study showed that women rheumatologists tend to work more as part-time physicians compared to their male counterparts [1], yet, this was not observed in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the female-to-male rheumatologist ratio is very high in some countries and is expected to rise in the future [19]. This might raise some concerns for the workforce in general as the ACR workforce study showed that women rheumatologists tend to work more as part-time physicians compared to their male counterparts [1], yet, this was not observed in the current study.…”
Section: Discussionmentioning
confidence: 59%
“…According to the Arab League of Associations for Rheumatology (ArLAR) Research Group (ARCH), the average number of rheumatologists in Arab countries is only 0.84 per 100,000 people. 7 In the northern region of Syria, there are only 0.07 rheumatologists available for every 100,000 people. This scarcity is similar to that of certain other countries such as Nicaragua (0.07 per 100,000 people), Pakistan, Nigeria (0.01 per 100,000 people), and India (0.01 per 100,000 people).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have been instrumental in the development of the specialty of Rheumatology in Africa. Ziade and colleagues have recently emphasized the importance of gender issues in Rheumatology (18). The inadequate recognition of the role of women Rheumatologists has also recently been raised (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%